Examining the Impact of Parallel Market Fluctuations on Penalty Rate Levels with Predictions of Depositors’ Behavior Regarding Deposit Failure Rates - Abbasian , Alireza; Chavoshi, Sayyed Kazem; Fallahshams , Mirfeiz; Gholami Jamkarani , Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This research aims to investigate the fluctuations of parallel markets on the level of penalty rates and to propose a conceptual model predicting depositors’ behavior regarding deposit failure rates. Theoretically, this study contributes to the development and presentation of factors affecting customers’ financial behavior in the banking system (both private and public). From an innovation perspective, the proposed model examines the actual decisions and behaviors of individuals in financial matters. Method: The research methodology is applied and post-event in nature. This study adopts a quantitative approach. The data used in this research were collected by referring to time series statistics from the central bank, official bank websites, and the country’s capital market and were utilized accordingly. The software used for data analysis in this research is Eviews. Findings: After the necessary data examination and analysis using the software, the results of this research indicate that in the first phase, the optimal portfolio was determined between currency rates, gold coins, real estate, securities, and bank deposits without imposing any penalty on long-term deposits. In this situation, individuals with different risk levels allocate 95%, 57%, and 37% of their portfolio to bank deposits, corresponding to risk-averse, moderate risk, and risk-seeking individuals, respectively. In the second phase, by imposing a penalty equal to 10% of the deposit profit, the optimal basket was determined; even in this case, these three groups of individuals with different risks allocate 88%, 53%, and 36% of their capital to bank deposits, respectively. Conclusion: It is observed that this decreasing trend in bank deposits continues until the penalty rate equals 25% of the bank deposit rate, beyond which no individual with any level of risk is willing to deposit in the bank.